2015
DOI: 10.1371/journal.pone.0130644
|View full text |Cite
|
Sign up to set email alerts
|

The ACTN3 R577X Polymorphism Is Associated with Cardiometabolic Fitness in Healthy Young Adults

Abstract: Homozygosity for a premature stop codon (X) in the ACTN3 “sprinter” gene is common in humans despite the fact that it reduces muscle size, strength and power. Because of the close relationship between skeletal muscle function and cardiometabolic health we examined the influence of ACTN3 R577X polymorphism over cardiovascular and metabolic characteristics of young adults (n = 98 males, n = 102 females; 23 ± 4.2 years) from our Assessing Inherent Markers for Metabolic syndrome in the Young (AIMMY) study. Both ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 49 publications
4
33
1
Order By: Relevance
“…In this study, measurements were mad of muscle strength (grip strength), muscle endurance (2-minute walking, dumbbell curl, and chair stand), flexibility (chair sit and reach, and back scratch test), agility (timed up-and-go), balance (one-leg standing), and VO 2 max. Previous studies have reported an association between the RR genotype of the ACTN3 R577X polymorphism and muscle power in elite athletes22 ) and ordinary people23 ) . In particular, the XX genotype is lower among power/sprint-oriented athletes than the RR genotype24 ) , and this finding is supported by the observation that individuals with the XX genotype show lower thigh muscle cross-sectional area than those with the RR and RX genotypes14 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, measurements were mad of muscle strength (grip strength), muscle endurance (2-minute walking, dumbbell curl, and chair stand), flexibility (chair sit and reach, and back scratch test), agility (timed up-and-go), balance (one-leg standing), and VO 2 max. Previous studies have reported an association between the RR genotype of the ACTN3 R577X polymorphism and muscle power in elite athletes22 ) and ordinary people23 ) . In particular, the XX genotype is lower among power/sprint-oriented athletes than the RR genotype24 ) , and this finding is supported by the observation that individuals with the XX genotype show lower thigh muscle cross-sectional area than those with the RR and RX genotypes14 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Alpha-actinin-3 is structural protein responsible for fast and powerful muscle contractions, and therefore at least one copy of the 577X allele is advantageous in sport disciplines associated with power/sprint type of physical activity (Ma et al 2013;Deschamps et al 2015). Also, the latest scientific data describe a role of this polymorphism, not only in all-cause mortality in humans, but also with increased survival time in patients with chronic heart failure, suggesting a potential extra-sarcomeric role for α-actinin-3 (Bernardez-Pereira et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recent data (BernardezPereira et al 2014) associate ACTN3 R577 allele with increased survival time in patients with chronic heart failure. The possible explanation could be the finding of extrasarcomeric ACTN3 expression in pulmonary artery, suggesting its potential role in the maintenance of vascular tone, and influencing the arterial BP (Deschamps et al 2015). Additionally, it is documented that the presence of X allele may lead to better endurance performance (Vincent et al 2007;Roth et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…23.7% vs. XX:15.9%, P = 0.011), suggesting that -actinin-3 deficiency may provide a certain survival advantage with age (Fiuza-Luces et al, 2011). Deschamps et al (2015) reported that young healthy individuals (both males and females; age = 23 ± 4.2 years) with the ACTN3 RR genotype exhibited higher resting systolic and diastolic blood pressure compared to individuals with the XX genotype. This implies that centenarians with the XX genotype may be less predisposed (i.e., more protected) to chronic diseases associated with high blood pressure, such as hypertension (Deschamps et al, 2015).…”
Section: Actn3 R577x Influence the Ageing Processmentioning
confidence: 99%
“…Deschamps et al (2015) reported that young healthy individuals (both males and females; age = 23 ± 4.2 years) with the ACTN3 RR genotype exhibited higher resting systolic and diastolic blood pressure compared to individuals with the XX genotype. This implies that centenarians with the XX genotype may be less predisposed (i.e., more protected) to chronic diseases associated with high blood pressure, such as hypertension (Deschamps et al, 2015). Several studies have now examined the impact of ACTN3 R577X on skeletal muscle traits and function in the ageing population, as reviewed recently in Pickering et al (2018).…”
Section: Actn3 R577x Influence the Ageing Processmentioning
confidence: 99%